Preparation method of double-layer ultrathin electrolyte membrane of all-solid-state battery based on transfer printing technology

Through the design of halide/sulfide double-layer electrolyte and gradient drying process, the preparation problem of multi-layer electrolyte membrane in all-solid state batteries is solved, the comprehensive performance of the battery is improved, and it is suitable for the industrial production of high-energy density solid state batteries.

CN120357020AActive Publication Date: 2025-07-22SHANGHAI FIRM LITHIUM NEW ENERGY TECH CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510500781.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-21
Publication Date
2025-07-22
Estimated Expiration
2045-04-21

AI Technical Summary

Technical Problem

The existing all-solid-state battery electrolyte membrane preparation technology is difficult to take into account both material cost and performance, and traditional transfer technology cannot achieve accurate composite and transfer of multi-layer electrolytes, resulting in peeling or cracking of the electrode sheet, which cannot meet the needs of all-solid-state batteries.

Method used

The halide/sulfide double-layer electrolyte design is adopted, and the substrate deformation is avoided through gradient drying process, and the interlayer binding force is enhanced. The ultra-thinning of the electrode sheet and the interface stability are achieved by transfer technology. The high voltage stability of the halide layer and the high ionic conductivity of the sulfide layer are combined to improve the battery performance.

Benefits of technology

It has achieved improvements in battery cycle life, rate performance and high temperature performance, and is suitable for the industrial production of high-energy density solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120357020A_ABST
    Figure CN120357020A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of an all-solid-state battery double-layer ultrathin electrolyte membrane based on a transfer printing technology. Through the design of halide / sulfide double-layer electrolyte, the cycle life of the battery is prolonged and the performance such as high rate performance is improved synergistically by utilizing the high voltage stability of the halide layer and the high ionic conductivity of the sulfide layer. Furthermore, a transfer printing process of the multi-layer electrolyte membrane is designed in a targeted manner, and a gradient drying process is utilized, so that deformation of the substrate can be avoided, interlayer cracking of halide / sulfide is effectively prevented, interlayer bonding force is enhanced, and ultra-thinness, high mechanical strength and interface stability of the pole piece are realized. Through material system optimization and transfer printing process innovation, the technical bottleneck that a double-layer electrolyte structure in an all-solid-state battery is difficult to apply is solved, and the method is suitable for industrial production of a high-energy-density solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid electrolytes, and relates to a method for preparing a double-layer ultra-thin electrolyte film of an all-solid-state battery based on a transfer technology. Background Art

[0002] All-solid-state batteries use solid electrolyte membranes to replace traditional liquid electrolytes and separators, and the core lies in the ion transport and interfacial stability of the electrolyte membrane. However, the current preparation technology of all-solid-state battery electrolyte membranes has the following problems: 1. It is difficult to balance material cost and performance: Although halide electrolytes have low cost and good affinity with the positive electrode, their interfacial stability with the negative electrode is insufficient when used alone; Sulfide electrolytes have excellent interfacial performance at the negative electrode, but they have high costs and are prone to side reactions with the positive electrode material. 2. Poor process compatibility: Most of the existing transfer technologies are for single-layer materials, and it is impossible to achieve precise compounding and transfer of multi-layer electrolytes, which cannot meet the requirements of all-solid-state batteries for two electrolyte membranes.

[0003] For the compounding of multi-layer electrolytes, most still use traditional coating technologies (such as slurry casting, lamination, etc.). The traditional coating technology directly coats on the surface of the negative or positive electrode sheet. Multi-layer coating is prone to peeling or cracking of the electrode sheet due to soaking, and it is difficult to achieve flat coating and thickness control. Therefore, there is an urgent need to develop a new transfer method for the compounding and transfer of multi-layer electrolyte membranes, and at the same time prepare all-solid-state battery electrolyte membranes that take into account material cost and performance and have good process compatibility. Summary of the Invention

[0004] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art, and provide a method for preparing a double-layer ultra-thin electrolyte film of an all-solid-state battery based on a transfer technology. First, through the design of a halide / sulfide double-layer electrolyte, it is made to contact the positive electrode and the negative electrode respectively, synergistically improving the performance of the battery such as cycle life and high-rate performance. Secondly, a new transfer process is developed for multi-layer electrolyte membranes. The gradient drying process can avoid substrate deformation, effectively prevent cracking between the halide / sulfide layers, and enhance the interfacial bonding force, realizing ultra-thin electrode sheets, high mechanical strength and interfacial stability, thereby being beneficial to improving the cycle life, high-rate performance and high-temperature performance of the battery.

[0005] The purpose of the present invention can be achieved by the following solutions:

[0006] In the first aspect, the present invention provides a method for preparing a double-layer ultra-thin electrolyte film of an all-solid-state battery based on a transfer technology, including the following steps:

[0007] S1. Dissolve a halide electrolyte and a sulfide electrolyte in an organic solvent with a binder respectively to obtain a halide electrolyte slurry and a sulfide electrolyte slurry;

[0008] S2. Coat a halide electrolyte slurry on the surface of the substrate and dry it to form a halide electrolyte layer;

[0009] S3. Coat a sulfide electrolyte slurry on the surface of the halide electrolyte layer and dry it to form a sulfide electrolyte layer, obtaining a substrate / electrolyte laminate;

[0010] S4. Align the negative electrode sheet with the substrate / electrolyte laminate, and after rolling, obtain the negative electrode sheet of the composite double-layer ultra-thin electrolyte film.

[0011] As an embodiment of the present invention, in step S1, the halide electrolyte includes one or more of Li3InCl6, Li3YCl6, Li4YI7, Li-Sc-Cl, Li-Ho-Cl; the sulfide electrolyte includes Li6PS5X, Li 10 GeP2S 12 、Li 3.25 Ge 0.25 P 0.75 S4、Li7P3S 11 One or more of them; wherein, X = Cl, Br, I.

[0012] As an embodiment of the present invention, in step S1, the D50 of the halide electrolyte is 3-20 μm; the D50 of the sulfide electrolyte is 2-20 μm.

[0013] As an embodiment of the present invention, in step S1, the organic solvent includes one or more of toluene, xylene, dibutyl ether; the binder includes one or more of polyisobutylene (PIB), styrene-butadiene rubber (BR).

[0014] As an embodiment of the present invention, in step S1, the addition amount of the organic solvent is 30%-50% of the weight of the electrolyte; the addition amount of the binder is 1%-5% of the weight of the electrolyte.

[0015] As an embodiment of the present invention, in step S1, both the halide electrolyte slurry and the sulfide electrolyte slurry are formed by ball milling or high-speed shear dispersion.

[0016] As an embodiment of the present invention, in step S2, the substrate includes PET.

[0017] As an embodiment of the present invention, in step S2, the coating thickness is controlled at 30-50 μm. The coating method of the present invention is the slot coating method.

[0018] As an embodiment of the present invention, in step S2, the drying temperature is 80 ± 5 °C, the time is 3-4 hours, and it is dried until the halide electrolyte layer is 8-15 μm.

[0019] As an embodiment of the present invention, in step S3, the coating thickness is controlled to be 30 - 60 μm.

[0020] As an embodiment of the present invention, in step S3, the drying temperature is 120 ± 5 °C, the time is 1 - 2 hours, and the drying is carried out until the sulfide electrolyte layer is 10 - 20 μm. High-temperature drying treatment can enable the solvent to volatilize rapidly, preventing the pole piece from delaminating or generating microcracks.

[0021] The gradient drying in the present invention includes the drying in steps S2 and S3. If the drying temperature is too low or too high, problems such as incomplete drying and microcracks on the pole piece may occur.

[0022] As an embodiment of the present invention, in step S4, the pressure of roll pressing is 10 - 50 MPa, and the temperature is 20 - 80 °C. During this process, the sulfide layer forms close contact with the surface of the negative electrode, and finally realizes the complete transfer of the electrolyte bilayer structure from the PET substrate to the negative electrode, with a transfer rate ≥ 98%.

[0023] In a second aspect, the present invention provides a double-layer ultra-thin electrolyte membrane for an all-solid-state battery obtained by the preparation method.

[0024] In a third aspect, the present invention provides an application of the double-layer ultra-thin electrolyte membrane for an all-solid-state battery in the preparation of an all-solid-state battery cell core.

[0025] As an embodiment of the present invention, the preparation process of the all-solid-state battery cell core includes: stacking, welding, and encapsulating the negative electrode pole piece of the composite double-layer ultra-thin electrolyte membrane for an all-solid-state battery with the positive electrode pole piece (NCM), and then the all-solid-state battery cell core is obtained.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. Through the design of the halide / sulfide double-layer electrolyte, the present invention utilizes the high-voltage stability of the halide layer and the high ionic conductivity (> 1 × 10 -3 S / cm) of the sulfide layer to synergistically improve the performance of the battery such as cycle life and high-rate performance; among them, the halide electrolyte membrane in contact with the positive electrode has a more stable interface, which can improve the performance of the battery such as cycle life and reduce the battery cost at the same time; the interface performance of the sulfide electrolyte membrane and the negative electrode is excellent, which can reduce the interface impedance (initial interface impedance < 8 Ω·cm 2 ), and improve the performance of the battery such as high-rate performance.

[0028] 2. The research of the present invention has found that traditional transfer technology is only applicable to the preparation and transfer of single-layer electrolyte membranes. When it comes to the compounding and transfer of multi-layer electrolyte membranes, traditional coating technology is mostly still used, but this technology has defects such as pole piece peeling or cracking. The present invention specifically designs a transfer process for multi-layer electrolyte membranes. The gradient drying process can avoid substrate deformation, effectively prevent cracking between the halide / sulfide layers, and enhance the interfacial bonding force. Among them, the low-temperature and long-time treatment in the first drying stage avoids solvent retention, and the secondary high-temperature treatment ensures rapid solvent volatilization, preventing pole piece delamination or the generation of microcracks, achieving pole piece ultra-thinning, high mechanical strength, and interfacial stability, thus being beneficial to improving the cycle life, high-rate performance, and high-temperature performance of the battery.

[0029] 3. Through the optimization of the material system and the innovation of the transfer process, the present invention solves the technical bottleneck of the difficult application of the double-layer electrolyte structure in all-solid-state batteries and is applicable to the industrial production of high-energy-density solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] By reading the detailed description of the non-limiting embodiments with reference to the following drawings, other features, objectives, and advantages of the present invention will become more apparent:

[0031] Figure 1 It is a flowchart for the preparation of the double-layer ultra-thin electrolyte membrane of the all-solid-state battery of the present invention;

[0032] Figure 2 It is an SEM image of the pole piece prepared in Example 1;

[0033] Figure 3 It is the cycle performance result of the battery cell prepared in Example 2;

[0034] Figure 4 It is the cycle performance result of the battery cell prepared in Comparative Example 1;

[0035] Figure 5 It is an SEM image of the pole piece prepared in Comparative Example 3;

[0036] Figure 6 It is an SEM image of the pole piece prepared in Comparative Example 4. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0037] The present invention will be described in detail below with reference to the drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, providing detailed implementation manners and specific operation processes, which will help those skilled in the art to further understand the present invention. It should be noted that the protection scope of the present invention is not limited to the following embodiments. Several adjustments and improvements made on the premise of the concept of the present invention all fall within the protection scope of the present invention.

[0038] The embodiments of the present invention provide a preparation method and cell assembly of a double-layer ultra-thin electrolyte film for all-solid-state batteries based on transfer printing technology, and its process reference Figure 1 .

[0039] Example 1: Preparation of electrode sheets

[0040] 1. Slurry preparation:

[0041] Halide layer slurry: Li3InCl6 powder (D50 = 5μm) is ball-milled and mixed with xylene solvent (40% of the powder weight) and PIB binder (3% of the powder weight);

[0042] Sulfide layer slurry: Li6PS5Cl powder (D50 = 3μm) is ball-milled and mixed with toluene solvent (35% of the powder weight) and BR binder (2% of the powder weight).

[0043] 2. Coating and drying:

[0044] Coat the halide layer (wet film thickness 30μm) on a 12μm PET substrate and dry it at 80°C for 3h to form a dense halide electrolyte layer (thickness 8μm, porosity < 5%);

[0045] Coat the sulfide layer (wet film thickness 40μm) and dry it at 120°C for 1.5h to form a sulfide electrolyte layer (thickness 12μm, ionic conductivity 1.2×10 -3 S / cm).

[0046] 3. Roll transfer printing:

[0047] Align the lithium metal negative electrode with the PET / electrolyte laminate and roll it at 20MPa and 60°C. The electrolyte layer is completely transferred to the surface of the negative electrode, and the total thickness of the electrode sheet ≤ 45μm (traditional wet electrode sheet > 60μm).

[0048] The thickness of the electrode sheet in this example is reduced by 25%, the tensile strength reaches 18MPa (traditional electrode sheet < 10MPa), and there are no cracks in the 180° bending test. It can be seen that Figure 2 by using the gradient drying process in this example, there are no micro-cracks at the interface of the prepared halide / sulfide double-layer electrolyte film, and the contact area between the sulfide layer and the lithium negative electrode > 95%.

[0049] Example 2: Preparation of cells

[0050] 1. Electrolyte design:

[0051] The halide layer (Li3InCl6) is used as a buffer layer on the positive electrode side to inhibit interfacial side reactions;

[0052] The sulfide layer (Li6PS5Cl) provides a high ionic conduction path (conductivity > 3×10 -3S / cm).

[0053] 2. Cell assembly:

[0054] Stack the lithium metal anode after transfer in Example 1, the cathode material composite of NCM811 and halide (loading 20 mg / cm 2 ), and the electrolyte layer, and cold press and form at 50 MPa, and package it into a soft-pack cell.

[0055] 2. Performance testing:

[0056] Cycling stability: The cycling stability is significantly improved compared with that using a sulfide electrolyte composite cathode. As Figure 3 can be seen, at 1C charge and discharge (2.5 - 4.3V), the capacity retention rate is 83% after 600 cycles (for traditional single-layer sulfide cells, due to the instability of the cathode at high voltage, it is < 70% after 500 cycles);

[0057] Rate performance: The discharge capacity at 5C reaches 88% of the discharge capacity at 0.2C (for traditional cells < 70%);

[0058] High-temperature performance: There is no lithium dendrite growth after cycling 500 times at 60°C, and the increase in interfacial impedance < 5%;

[0059] 3. Mechanism analysis:

[0060] Double-layer synergistic effect: The halide layer blocks the oxidation of the sulfide layer by the cathode active material, and the sulfide layer reduces the interfacial impedance (initial interfacial impedance < 8 Ω·cm 2 ). Based on the double-layer electrolyte interface optimization and pressure transfer process in this example, long cycling life and high rate performance of all-solid-state cells are achieved.

[0061] 4. Conclusion: Example 1 significantly improves the mechanical properties of the electrode sheet through the ultra-thin multi-layer structure design. Example 2 verifies the optimization effect of the double-layer electrolyte on the comprehensive performance of all-solid-state batteries. Both have clear industrial application values.

[0062] Comparative Example 1

[0063] The preparation method of the electrolyte in this comparative example is basically the same as that in Example 1, except that the halide electrolyte layer is omitted, and only the sulfide electrolyte layer is retained. The negative electrode sheet with the obtained composite sulfide electrolyte layer is used to prepare a soft-pack cell with reference to Example 2. From Figure 4 it can be seen that at 1C charge and discharge (2.5 - 4.3V), the capacity retention rate is 82% after 300 cycles, indicating that the lack of the halide electrolyte layer will cause decomposition and instability at the cathode interface.

[0064] Comparative Example 2

[0065] The preparation method of the electrolyte in this comparative example is basically the same as that in Example 1, except that the sulfide electrolyte layer is omitted, and only the halide electrolyte layer is retained. The negative electrode sheet of the obtained composite halide electrolyte layer was used to prepare a soft-pack battery cell with reference to Example 2. The results show that when the halide electrolyte layer is in direct contact with the lithium metal negative electrode, the battery will short-circuit and cannot participate in the cycle normally.

[0066] Comparative Example 3

[0067] The preparation method of the electrolyte in this comparative example is basically the same as that in Example 1, except that the drying in Step 2 is drying at 120 °C for 3 h. As Figure 5 shown, Comparative Example 3 did not adopt the gradient drying process, resulting in obvious microcracks at the interface of the prepared halide / sulfide bilayer electrolyte membrane, which affected the performance of the subsequent battery, such as cycle life, high-rate performance, and high-temperature performance.

[0068] Comparative Example 4

[0069] The preparation method of the electrolyte in this comparative example is basically the same as that in Example 1, except that the drying in Step 3 is drying at 80 °C for 1.5 h. As Figure 6 shown, Comparative Example 4 did not adopt the gradient drying process, resulting in obvious microcracks at the interface of the prepared halide / sulfide bilayer electrolyte membrane, which affected the performance of the subsequent battery, such as cycle life, high-rate performance, and high-temperature performance.

[0070] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various deformations or modifications within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A preparation method of a double-layer ultra-thin electrolyte film for an all-solid-state battery based on a transfer technology, characterized in that, It includes the following steps: S1. Dissolve the halide electrolyte and the sulfide electrolyte respectively with a binder in an organic solvent to obtain a halide electrolyte slurry and a sulfide electrolyte slurry; S2. Coat the halide electrolyte slurry on the surface of the substrate and dry to form a halide electrolyte layer; S3. Coat the sulfide electrolyte slurry on the surface of the halide electrolyte layer and dry to form a sulfide electrolyte layer, obtaining a substrate / electrolyte laminate; S4. Align the negative electrode sheet with the substrate / electrolyte laminate, and after rolling, obtain a negative electrode sheet with a composite double-layer ultra-thin electrolyte membrane.

2. The preparation method according to claim 1, characterized in that In step S1, the halide electrolyte includes one or more of Li3InCl6, Li3YCl6, Li4YI7, Li-Sc-Cl, and Li-Ho-Cl; the sulfide electrolyte includes one or more of Li6PS5X, Li 10 GeP2S 12 、Li 3.25 Ge 0.25 P 0.75 S4, Li7P3S 11 ; wherein, X = Cl, Br, I; The D50 of the halide electrolyte is 3 - 20 μm; the D50 of the sulfide electrolyte is 2 - 20 μm.

3. The preparation method according to claim 1, characterized in that, In step S1, the organic solvent includes one or more of toluene, xylene, and dibutyl ether; the binder includes one or more of polyisobutylene and styrene-butadiene rubber; The addition amount of the organic solvent is 30% - 50% of the weight of the electrolyte; the addition amount of the binder is 1% - 5% of the weight of the electrolyte.

4. The preparation method according to claim 1, wherein In step S1, the addition amount of the organic solvent is 30% - 50% of the weight of the electrolyte; the addition amount of the binder is 1% - 5% of the weight of the electrolyte.

5. The preparation method according to claim 1, wherein In step S2, the substrate includes PET.

6. The preparation method according to claim 1, characterized in that, In step S2, the drying temperature is 80 ± 5 °C, the time is 3 - 4 hours, and it is dried until the halide electrolyte layer is 8 - 15 μm.

7. The preparation method according to claim 1, wherein In step S3, the drying temperature is 120 ± 5 °C, the time is 1 - 2 hours, and it is dried until the sulfide electrolyte layer is 10 - 20 μm.

8. The preparation method according to claim 1, characterized in that, In step S4, the rolling pressure is 10 - 50 MPa, and the temperature is 20 - 80 °C.

9. A double-layer ultra-thin electrolyte membrane of a all-solid-state battery obtained by the preparation method according to any one of claims 1 - 8.

10. Use of the double-layer ultra-thin electrolyte film of the all-solid-state battery as described in claim 9 in the preparation of an all-solid-state battery cell, characterized in that, The preparation process of the all-solid-state battery cell includes: stacking, welding, and encapsulating the negative electrode sheet with the composite double-layer ultra-thin electrolyte membrane of the all-solid-state battery and the positive electrode sheet, then the all-solid-state battery cell is obtained.

Citation Information

Patent Citations

  • Composite solid electrolyte film and preparation method and application thereof

    CN115458801A

  • Ultrathin electrolyte membrane complex, preparation method thereof and solid-state battery

    CN116826181A

  • Composite electrolyte layer, preparation method thereof and solid-state battery

    CN117059882A

  • Double-layer solid electrolyte membrane, preparation method thereof and all-solid-state battery

    CN119627200A

  • Method for manufacturing sulfide all-solid battery

    JP2014241240A